Nutritional Status and Anemia: A Study in Adolescent Girls - Lusi Lestari; Heni Marliany; Pebri Yuliantini; Sandriani Sandriani (LPPM STIKes Muhammadiyah Ciamis, 2026)
Introduction: Anemia remains a common public health problem among adolescents, characterized by low hemoglobin levels. This group is more vulnerable due to menstruation, rapid growth, and increased iron requirements, which are often not balanced with a healthy diet. Furthermore, the perception of a less-than-ideal body image encourages adolescent girls to restrict their diet, resulting in suboptimal nutritional status. However, nutritional status plays a crucial role in the incidence of anemia because it is related to iron adequacy in the body. Therefore, it is necessary to examine the relationship between nutritional status and the incidence of anemia in adolescent girls as a preventative measure. Objective: This study aims to determine the relationship between nutritional status and the incidence of anemia in adolescent girls. Method The study used an analytical observational design with a cross-sectional approach, involving 47 grade VIII female adolescents at SMPN 5 Ciamis in 2026, who were taken using simple random sampling. Nutritional status was measured using Body Mass Index for age (BMI/A), while anemia was measured based on hemoglobin levels (Hb <12 g/dL). Data analysis was performed using the Chi-Square test with a significance level of 0.05. Result: The results of the study showed that the majority of respondents had normal nutritional status (48.9%) and did not have anemia (55.3%). However, 38.3% of adolescents had poor nutritional status and 44.7% had anemia. Bivariate analysis revealed a significant association between nutritional status and the prevalence of anemia (p = 0.008). Conclusion: This study confirms that nutritional status plays a crucial role in the development of anemia in adolescent girls. Therefore, schools and health professionals should promote balanced nutrition rich in iron and provide targeted health education about anemia prevention to adolescent girls.